Infecção pelos vírus da hepatite B e hepatite C entre portadores de diabetes melito no Hospital Universitário João de Barros Barreto - NUNES, Alessandro de Sousa (2023)
This research was conducted during the period from June 2007 to February 2008, to study the prevalence of hepatitis B virus and hepatitis C virus infections in patients with diabetes mellitus, attended at Hospital Universitário João de Barros Barreto, in Belém city, Pará, as well as investigate their socio-demographic profile and possible risk situations for these infections. At the end of that established period, were included 69 individuals, which formed the present sample. Each participant was implemented a standardized questionnaire to obtain information about their socio-demographic characteristics and the different risk situations. Then, each participant received a printed request for blood examinations which were collected in the hospital laboratory. The participants were investigated for the serologic test following: HBsAg, anti-HBc total, anti-HBs and anti-HCV. In the sample investigated it was found a predominance of the female population, with 63.8% (44/69), and participants over 40 years old (84.0%). They have fixed partner 60.9% (42/69) and 66.7% (46/69) of respondents revealed not had completed, at least, the primary school. Revealed have been born in Pará 85.5% (59/69) of the participants, 42.0% (29/69) were retirees, and the family income was up 02 prevailing minimum wages, with 68.1% (47/69) of respondents. Slightly more than half of the group (51.6% - 33/64) was diagnosed with diabetes mellitus had more than 10 years and, among those who used hypoglycemic drugs, 52.4% (33/63) were using insulin subcutaneously and 47.6% (30/63) used only oral hypoglycemic agents. The home capillary blood glucose control was conducted by 8.7% (6/69) patients and 58.0% (40/69) never have been vaccinated have shown for hepatitis B. As for high-risk situations surveyed, 87.0% (60/69) have revealed surgical history, 22.2% (14/63) of those with sexual experience had venereal disease history and 82.5% (52/63) of these never revealed have used condoms. The overall prevalence of infection with hepatitis B virus was 37.7%, 1.4% for HBsAg, 31.9% for anti-HBc and 5.8% for anti-HBs. For the Hepatitis C virus, the prevalence was 2.9%. The figures for the prevalence found for both viruses were not divergent found in the Brazilian general population. The prevalence hepatitis B virus infection found is similar to that observed in the general population. About the anti-HCV, however, their prevalence was higher than that demonstrated in some Brazilian studies based on the general population.